1996
DOI: 10.1021/jp960640h
|View full text |Cite
|
Sign up to set email alerts
|

C60 as a Photocatalyst of Electron-Transfer Processes:  Reactions of Triplet C60 with Chloranil, Perylene, and Tritolylamine Studied by Flash Photolysis and FT-EPR

Abstract: Photoprocesses in benzonitrile solutions of C60 and chloranil (CA) have been studied by complementary techniques of nanosecond laser photolysis and Fourier transform EPR. Direct oxidation of 3C60 by CA is slow (k = (2.0 ± 0.3) × 107 M-1 s-1), consistent with the high oxidation potential of 3C60. However, the formation rate and yield of CA- are much increased by addition of perylene (Pe) or tritolylamine (TTA) via the fast reactions 3C60 + Pe → C60 + 3Pe, followed by 3Pe + CA → Pe+ + CA-, or 3C60 + TTA → C60 - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
107
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 30 publications
6
107
1
Order By: Relevance
“…20 The ratios show the saturation upon increasing the concentration of the free radicals, as shown in Figure 6. 19,20 At sufficiently high concentrations of the free radicals above ca.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…20 The ratios show the saturation upon increasing the concentration of the free radicals, as shown in Figure 6. 19,20 At sufficiently high concentrations of the free radicals above ca.…”
Section: Resultsmentioning
confidence: 87%
“…Finally, the electron-transfer rate constants (k et ) are obtained from k et ) Φ et k q as listed in Table 2. 20 The k et values are considerably smaller than the diffusion-controlled limit (k diff ) 5.2 × 10 9 M -1 s -1 in PhCN), 21 although the ∆G°e t values calculated from the Rehm-Weller equation are all sufficiently negative (Table 1) to predict the diffusion-controlled secondorder rate constants for the electron-transfer processes.…”
Section: Resultsmentioning
confidence: 98%
“…The addition of TMB resulted in the appearance and a considerable increase in limitation with an increase in the concentration of the additive. Evidently, the limitation observed can be considered as evidence for the formation of the ë 60 radical anion, which strongly absorbs radiation at the excitation wavelength ( ε ≅ 18000 l mol -1 cm -1 [16]). In this case, the formation of can be due only to two-photon absorption in accordance with scheme (2), since ë 60 does not exhibit absorption from the ground state in the given spectral region.…”
Section: Resultsmentioning
confidence: 92%
“…The probable course If this solution were used for the limitation of firstharmonic radiation from a YAG : Nd 3+ laser, it would be a more efficient limiter than a solution without Per additives. The Per radical cation, whose absorption band maximum lies in the region 535-545 nm ( ε ≅ 50 000 l mol -1 cm -1 [15,16]), is also a product of reaction (3). Because of this, this solution is also promising in terms of the limitation of second-harmonics radiation from a YAG : Nd 3+ laser.…”
Section: Resultsmentioning
confidence: 99%
“…17 In the present study, we employed three aromatic amines such as triphenyl amine (TPA), tri-p-tolylamine (TTA), and 1,1-bis(di-4-tolylaminophenyl)cyclohexane (TAPC) (structures are shown in Scheme I). These amines are considered to be interesting electron donors; [18][19][20] especially, TAPC includes two triphenyl amine moieties in the same molecule. 9,10 It has been reported that TAPC shows high hole mobility (10 -2 cm 2 /Vs) in vapor deposited thin films, [21][22][23] photoconducting properties, 8 and charge-generating and hole-transporting properties in electroluminescence devices.…”
Section: Introductionmentioning
confidence: 99%